SEMIOTIKA FISKE TERHADAP IDEOLOGI PATRIOTISME FILM "GUNDALA" - Adhitiya Prasta Pratama (JADECS (Journal of Art, Design, Art Education & Cultural Studies), 2022)
This writing aims to reveal the ideology of patriotism in the film Gundala. Namely, when today's film can be reached as a social practice and a medium of mass communication. The problem that is focused on is understanding the signs, meanings, and codes contained in the film's scenes. This paper also describes the history of film in Indonesia and its practice. In order to explore the study of signs and codes in films, this paper uses John Fiske's semiotic unit analysis, namely through the stages of reality, representation, and ideology. The data obtained through search searches, which are sourced from Google and Telegram, and analyzed descriptively qualitatively. This writing concludes that today's film can deconstruct the unity of meaning, symbol, and code in exposing its naturalness as an ideological construction.